2018
DOI: 10.5194/hess-2018-318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the impacts of human water use and climate variations on recent drying of Lake Urmia basin: the value of different sets of spaceborne and in-situ data for calibrating a hydrological model

Abstract: Abstract. During the last decades, the endorheic Lake Urmia basin in northwestern Iran has suffered from decreased precipitation, groundwater levels and a very strong reduction in the volume and more recently also in the extent of Lake Urmia.Human water use has exacerbated the desiccating impact of climatic variations. This study quantifies the contribution of human water use to the reduction of inflow into Lake Urmia, to the loss of lake water volume and to the loss of groundwater and total water storage in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The reduction in rainfall along with decreasing groundwater tables and a rising population in the basin will likely exert growing pressure to continue diverting stream flow before it reaches Lake Urmia. Over the last two decades, it was sharply dried and its surface reduced about 80% from 2003 [5]. The water table of Lake Urmia was decreased severely in recent years which caused serious socio-environmental consequences [4].…”
Section: The Lake Urmiamentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in rainfall along with decreasing groundwater tables and a rising population in the basin will likely exert growing pressure to continue diverting stream flow before it reaches Lake Urmia. Over the last two decades, it was sharply dried and its surface reduced about 80% from 2003 [5]. The water table of Lake Urmia was decreased severely in recent years which caused serious socio-environmental consequences [4].…”
Section: The Lake Urmiamentioning
confidence: 99%
“…Hosseini-Moghari using spatial and hydrology and in situ data assessed the contribution of human acts to the decline of inflow water for the lake, the groundwater table reduction, and water storage in the lake reservoir [5]. They found that 50% of the total basin water loss is due to sectorial management of water resources in the region.…”
Section: The Lake Urmiamentioning
confidence: 99%
“…Overuse of irrigation in the basin coupled with a recent drought has resulted in decreased environmental flows to Lake Urmia and led to continued shrinking of the lake (Hosseini-Moghari et al, 2018;Moshir Panahi et al, 2020;Schulz et al, 2020). As such, environmental flow requirements for Urmia lake are in direct competition with agricultural water demand.…”
Section: Introductionmentioning
confidence: 99%
“…Hosseini‐Moghari et al . (2018) quantified the effect of human water use in reducing the inflow into Urmia Lake. They discovered that even if human water use were eliminated completely, Urmia Lake would have a significant loss of water caused by drought.…”
Section: Introductionmentioning
confidence: 99%